Causes or tax reform in Latin America, 1977-95 - Mahon, James E.
Among the policy changes associated with neoliberalism in Latin America, tax reform has played a leading role as it has been crucial not only to price stabilization but also to managing economic liberalization. This paper seeks to determine its causes more precisely by analyzing data from fifteen Latin American contries from 1977 to 1995